Accumulation of 24 nucleotide transgene‐derived siRNAs is associated with crinivirus immunity in transgenic plants. (26th July 2018) - Qiao, Wenjie; Zarzyńska‐Nowak, Aleksandra; Nerva, Luca; Kuo, Yen‐Wen; Falk, Bryce W.
Summary: RNA silencing is a conserved antiviral defence mechanism that has been used to develop robust resistance against plant virus infections. Previous efforts have been made to develop RNA silencing‐mediated resistance to criniviruses, yet none have given immunity. In this study, transgenic Nicotiana benthamiana plants harbouring a hairpin construct of the Lettuce infectious yellows virus (LIYV) RNA‐dependent RNA polymerase (RdRp) sequence exhibited immunity to systemic LIYV infection. Deep sequencing analysis was performed to characterize virus‐derived small interfering RNAs (vsiRNAs) generated on systemic LIYV infection in non‐transgenic N. benthamiana plants as well as transgene‐derived siRNAs (t‐siRNAs) derived from the immune‐transgenic plants before and after LIYV inoculation. Interestingly, a similar sequence distribution pattern was obtained with t‐siRNAs and vsiRNAs mapped to the transgene region in both immune and susceptible plants, except for a significant increase in t‐siRNAs of 24 nucleotides in length, which was consistent with small RNA northern blot results that showed the abundance of t‐siRNAs of 21, 22 and 24 nucleotides in length. The accumulated 24‐nucleotide sequences have not yet been reported in transgenic plants partially resistant to criniviruses, and thus may indicate their correlation with crinivirus immunity. To further test this hypothesis, we developed transgenic melon ( Cucumis melo ) plants immune to systemic infection of another crinivirus, Cucurbit yellow stunting disorder virus (CYSDV). As predicted, the accumulation of 24‐nucleotide t‐siRNAs was detected in transgenic melon plants by northern blot. Together with our findings and previous studies on crinivirus resistance, we propose that the accumulation of 24‐nucleotide t‐siRNAs is associated with crinivirus immunity in transgenic plants.